2022
DOI: 10.11591/ijere.v11i2.22237
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Google Classroom to increase students’ information literacy

Abstract: Information literacy at the higher education level is very important because it tends to be problematic in fostering students' critical thinking skills, including awareness, collection, understanding, analysis, synthesis, and the use of information and their attitudes to the treatment of information at the university level. This study examined the effects of the online learning Google Classroom in enhancing information literacy among students. This study observed a one-group pretest-posttest experimental desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
0
11
0
3
Order By: Relevance
“…Critical thinking has become one of the tools used in everyday life to solve a problem because it involves the ability to reason, interpret, and the ability to evaluate information to allow making a valid and trusted decision [7][8] [9]. Critical thinking processes can also train students to draw conclusions and synthesize information [10] [11] [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Critical thinking has become one of the tools used in everyday life to solve a problem because it involves the ability to reason, interpret, and the ability to evaluate information to allow making a valid and trusted decision [7][8] [9]. Critical thinking processes can also train students to draw conclusions and synthesize information [10] [11] [12].…”
Section: Introductionmentioning
confidence: 99%
“…Students are still expected to memorize formulas and answer questions correctly in chemistry class without being encouraged to think critically and creatively [15]. Learning media is less effective, and understanding leads to memorization [11]. Students are less motivated to develop their thinking skills using conventional media [10].…”
Section: Introductionmentioning
confidence: 99%
“…One of the characteristics of digital literacy possessed by students is mastery of digital technology devices [51]. Digital literacy becomes better if it can be developed in real-life situations, especially in solving problems, including student assignments [85]. Digital literacy competence is essential because: a) emphasis on raising awareness of thinking in critically evaluating information; b) emphasis on improving the ability to create digital information; c) emphasis the mastery of other skills in the form of computers, the internet, text, media, visual, audio, or the web presented through digital technology devices [41] [42].…”
Section: The Importance Of Digital Literacy For Studentsmentioning
confidence: 99%
“…The reason is that in the field of media literacy, it was revealed that teachers rarely use Information and Technology-based learning media, such as android-based e-modules [58][66] [75][89] [90]; this happens due to the lack of facilities and infrastructure available in learning media, and the lack of understanding and skills of teachers in designing android-based e-learning learning media. In the field of information literacy, the ability of teachers and school and campus library staff is currently inadequate [21] [85]. In addition, the lack of quality teacher-student interaction in the learning process [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation